Dissolved-Cl2 triggered redox reaction enables high-performance perovskite solar cells - Yujie Luo; Kaikai Liu; Liu Yang; Wenjing Feng; Lingfang Zheng; Lina Shen; Yongbin Jin; Zheng Fang; Peiquan Song; Wanjia Tian; Peng Xu; Yuqing Li; et al. (Nature Communications, 2023)
Abstract Constructing 2D/3D perovskite heterojunctions is effective for the surface passivation of perovskite solar cells (PSCs). However, previous reports that studying perovskite post-treatment only physically deposits 2D perovskite on the 3D perovskite, and the bulk 3D perovskite remains defective. Herein, we propose Cl2-dissolved chloroform as a multifunctional solvent for concurrently constructing 2D/3D perovskite heterojunction and inducing the secondary growth of the bulk grains. The mechanism of how Cl2 affects the performance of PSCs is clarified. Specifically, the dissolved Cl2 reacts with the 3D perovskite, leading to Cl/I ionic exchange and Ostwald ripening of the bulk grains. The generated Cl− further diffuses to passivate the bulk crystal and buried interface of PSCs. Hexylammonium bromide dissolved in the solvent reacts with the residual PbI2 to form 2D/3D heterojunctions on the surface. As a result, we achieved high-performance PSCs with a champion efficiency of 24.21% and substantially improved thermal, ambient, and operational stability.